Erythrocyte Aging, Protection via Vesiculation: An Analysis Methodology via Oscillatory Flow - Asaro, Robert J.; Zhu, Qiang; Cabrales, Pedro (Frontiers in Physiology, 2018)
We introduce a novel theoretical-simulation-experimental approach to subject erythrocytes to tailored shear deformations that, mimic the types of deformations that promote vesiculation. We demonstrate that deformations, specifically as occur in splenic flow [1], and of the type that promote vesiculation can be caused by simple, yet tailored, oscillatory shear flow. We show that such oscillatory shear flow provides an ideal environment to explore a wide variety of metabolic and biochemical effects that promote vesiculation. Deformation details, typical of splenic flow, such as in-folding and implications for membrane/skeleton interaction are demonstrated and quantitatively analyzed. We introduce a theoretical, essentially analytical, vesiculation model that directly couples to our more complex numerical, multilevel, model that clearly delineates various fundamental elements, i.e. sub-processes, that are involved and mediate the vesiculation process. This model highlights important vesiculation precursors such as areas of membrane/skeleton disruptions that trigger the process. We demonstrate, via flow cytometry, that the deformations we experimentally induce on cells, and numerically simulate, do not induce lethal forms of cell damage but do induce vesiculation as theoretically forecasted. This, we demonstrate, provides a direct link to cell membrane/skeletal damage such as is associated with metabolic and aging damage. An additional noteworthy feature of this approach is the avoidance of artificial devices, e.g. micro-fluidic chambers, in which deformations and their time scales are unrepresentative of physiological processes such as splenic flow.